Interaction between foreign exchange market and capital market fluctuations - Ghayeghi Hassani, Fatemeh; Kheradyar, Sina; Mashki, Mehdi (International Journal of Business Management and Entrepreneurship, 2022)
Over the past few years, we have witnessed intensive fluctuations and changes in our exchange market, which have deeply affected different economic foundations of our country. Following these fluctuations, capital markets have also changed profoundly, and they have had occasional interactions with exchange markets. The purpose of this research is to investigate how and to what extent these markets are connected and what are their interactions. In this research, aside from the effects of temporal factors in each market, the concurrent relationships between capital and exchange markets and their interactive effects were also examined. The data used for this research was gathered from an eleven-year period between Mar. 2008 and Feb. 2019, and has been checked on a monthly basis. Two multivariate regression models were analyzed by Eviews10 program. The outcome of the analysis of regression models using ARMA method, in accordance with first, second and third hypotheses, showed that previous-period fluctuations of the capital market have a meaningful, negative correlation with future fluctuations of this market, and as the fluctuations in the previous period increase, the future fluctuations decrease, but the fluctuations of exchange market don’t cause a con-current effect on capital market fluctuations. The results of the fourth, fifth and sixth hypotheses show that the fluctuations in the previous period of the exchange market have a positive and meaningful effect on the future fluctuations of this market, and as the fluctuations increase in the previous period, the future fluctuations also increase. Also, the previous period fluctuations of the exchange market have a positive, meaningful and interactive effect on the capital market and exchange market fluctuations, but in return, the fluctuations in the capital market do not cause a concurrent turmoil in the exchange market.